Sintesis ZSM-5 Menggunakan Silika Presipitasi Dari Fly Ash Pabrik CPO - Saputra, Rio; Saputra, Edy; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm fly ash is waste in the palm oil industry. Palm fly ash has high content of silica. ZSM-5 is one of synthetic zeolite which used as catalyst. It can be synthesized from silica and alumina using hidrothermal method. Source of silica that can be used to ZSM-5 synthesis are sodium silicate, gelled silica and precipitated silica. the purpose of this research is to synthesis ZSM-5 using precipitated silica hydrothermally. The result was analyzed using FTIR. ZSM-5 can be synthesized using precipitated silica hydrothermally. Based on infrared spectrum,the product synthesis shows four characteristic of ZSM-5 characters.Key words : fly ash, silica, hydrothermal and ZSM-5